Reformulating Strategies to Develop Democratization through Civic Education in Aceh - Anton Widyanto (Ulumuna, 2017)
This paper aims to pursue appropriate strategies to shape students’ characters and sense of nationalism through formal education in Aceh. Grounded in the structured interviews, focused group discussions, and observations, this qualitative case study reveals that Aceh, as one province in Indonesia, which was trapped in prolonged army conflict, needs character education that focuses on the nation-state paradigm. The contemporary Acehnese society is also facing new cultural, ethnic, inter-religious conflicts, as well as internal conflicts among Muslims. The seed of these conflicts becomes increasingly worse when infiltrated by the contemporary political interests in the province. During the era of military conflict, Pendidikan Moral Pancasila (Pancasila Moral Education) was deemed “a dangerous” subject to be taught in Aceh schools due to its contradictory nature against the ideology of Gerakan Aceh Merdeka (Free Aceh Movement). Despite downgrading the students’ spirit of nationalism, such situation has gradually been changed since a peace agreement between the two parties, Indonesian government and Gerakan Aceh Merdeka, was achieved in August 2005. Nevertheless, this demonstrates the need to overhaul curriculum and instructional strategies in the pursuit of the democratization in the province.